Effect of a Defined Competitive Exclusion Culture for Prophylaxis and Reduction of Horizontal Transmission of Salmonella enteritidis in Broiler Chickens - Wolfenden, A.D.; Vicente, J.L.; Bielke, L.R.; Pixley, C.M.; Higgins, S.E.; Donoghue, D.J.; Donoghue, A.M.; Hargis, B.M.; Tellez, G. (International Journal of Poultry Science, 2007)
Effective Competitive Exclusion (CE) cultures have been shown to accelerate development of normal microflora in chicks and poults, providing increased resistance to infection by some enteric bacterial pathogens. Our objective was to develop a CE culture for prophylaxis and reduced horizontal transmission of Salmonella enteritidis (SE) in broiler chickens. In the present study, seven members of the family Enterobacteriaceae and 2 lactic acid bacteria isolates, each capable of in vitro and in vivo inhibition of SE, were selected and combined to form the putative CE culture. In the first experiment, day-of-hatch chicks were randomly divided into four pens. All treated chicks were orally gavaged with the CE culture and 3 pens were treated with the CE culture in the drinking water for four consecutive days. Treated and control-non treated chicks were challenged with SE on day 4. All 3 groups of birds that were treated with the CE culture had a significant decrease (p<0.05) in cecal colonization compared with non-CE-treated SE-challenged chicks. Two additional experiments were designed to measure the efficacy of the CE culture in reducing SE horizontal transmission from infected to uninfected chicks when commingled. SE was recovered in the cecal tonsils with a significantly lower incidence at days 7 and 14 in Experiment 2 and day 7 in Experiment 3 from the groups that received the CE in the drinking water as compared to controls respectively. These results suggest that a relatively simple and defined CE culture can reduce SE colonization in neonatal chicks.